Mean Platelet Volume and Immature Platelet Fraction in Autoimmune Disorders - Schmoeller, Deonilson; Picarelli, Maria Mercedes; Paz Munhoz, Terezinha; Poli de Figueiredo, Carlos Eduardo; Staub, Henrique Luiz (Frontiers in Medicine, 2017)
Mean platelet volume (MPV), measured using automated blood analysers, has been appraised as a potential biomarker in cardiovascular disease, diabetes mellitus, and cancer. The test, a useful tool in differentiation of thrombocytopenic states, has now been carried out for autoimmune disorders, but data are yet scarce. Controversial results have been obtained in systemic and organ-specific autoimmune disorders. Another test, the immature platelet fraction (IPF) reflects the amount of young, reticulated platelets. IPF is calculated by automated hematology analysis or flow cytometry, and it is usually high in patients with rapid platelet destruction. For both MPV and IPF, standardization of cutoff is a major need. In this review, we focus the current applicability of MPV and IPF as biomarkers in patients with autoimmune diseases.